PENERAPAN KURIKULUM MERDEKA BELAJAR PADA PEMBELAJARAN PAI DI SDN 056600 GANG KENANGA - Fitri Handayani (Journal of Community Devation, 2025)
Seeing the decreasing quality of education, the Minister of Education and Culture launched an independent learning curriculum as a solution to improve the quality of education in Indonesia. With this independent learning curriculum, it will be a complement to the previous curriculum. This independent learning curriculum is also a starting point for changes to the PAI learning concept which so far has been assessed as learning that only prioritizes character education, so it is considered very monotonous and boring for students. This causes students to be less enthusiastic about participating in learning. The aim of this research is to determine the application of the independent learning curriculum in PAI learning at SDN 056600 Gang Kenanga , from the planning stage, implementation stage and evaluation stage. This research uses descriptive qualitative field research methods. The location used as the research site is SDN 056600 Gang Kenanga  which is located in Baturraden District, Banyumas Regency. With research subjects: Education Manager, School Principal, Class IV facilitator and Koran teacher. For data collection techniques, researchers used observation, interviews and documentation methods. The results of the research regarding the implementation of the independent learning curriculum in PAI learning at SDN 056600 Gang Kenanga  are: First, at the planning stage the facilitator made a lesson plan for indoor learning activities. Weekly plan and The yearly plan for outdoor learning is adjusted to CP, TP and ATP in PAI learning. Second, the implementation stage of PAI learning with the independent learning curriculum is carried out through indoor and outdoor learning, for indoor activities in the form of delivering PAI material in the classroom, then for outdoor activities in the form of classroom exploration, farming, market day, outbound, Qur'anic camp and this live study. Third. The evaluation stage, for evaluating PAI learning, is carried out with a summative assessment for indoor activities and a formative assessment for outdoor activities.